Blood oranges maintain bioactive compounds and nutritional quality by postharvest treatments with γ-aminobutyric acid, methyl jasmonate or methyl salicylate during cold storage. (15th February 2020) - Habibi, Fariborz; Ramezanian, Asghar; Guillén, Fabián; Serrano, María; Valero, Daniel
Highlights: Postharvest treatments with GABA, MeJA and MeSA maintained the bioactive compounds. MeSA at 100 μmol L −1 maintained bioactive compounds of blood orange during storage. Anthocyanin in the treated fruit were higher than control samples due to higher PAL/PPO activities. Non-enzymatic system was major part of antioxidant activity in blood orange fruit. MeSA and MeJA vapor treatment were more effect than vacuum infiltration of GABA. Abstract: The effects of postharvest treatments with γ-aminobutyric acid (GABA), methyl jasmonate (MeJA) or methyl salicylate (MeSA) on antioxidant systems and sensory quality of blood oranges during cold storage were evaluated (150 days at 3 °C plus 2 days at 20 °C, shelf life). Fruit firmness, titratable acidity (TA), total antioxidant activity (TAA) and ascorbic acid (AA) decreased during cold storage, all these changes being delayed in treated fruit, with the greatest differences observed with the 50 µmol L −1 MeJA and 100 µmol L −1 MeSA treatments. Total phenolic content (TPC), total anthocyanin content (TAC) and the major individual anthocyanins, cyanidin 3-glucoside and cyanidin 3-(6″-malonylglucoside), were found at higher concentration in treated fruit than in control during the whole cold storage period. Overall, 100 µmol L −1 MeSA was the most effective for maintaining fruit quality and maintained higher anthocyanin concentration due to higher phenylalanine ammonia-lyase (PAL) and lower polyphenol oxidase (PPO) activities.